The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1748-1716.1978.tb06206.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and contraction properties of cat lumbar back muscles

Abstract: The gross morphology, innervation pattern and contraction properties of lumbar back muscles in the cat were investigated. The medially located multifidi and interspinales are formed by short bundles interconnecting adjacent vertebrae. Laterally located bundles composing longissimus and iliocostalis are attached to the spinous processes by a fascial layer and to the pelvic bone by a well developed intermuscular septum. Different spinal segments innervate the various sections along the muscles in such a way that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…There is considerable information available on the histochemical and functional organization of mam malian limb muscles while relatively few studies have been made on normal lumbar spinal muscle [4,5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable information available on the histochemical and functional organization of mam malian limb muscles while relatively few studies have been made on normal lumbar spinal muscle [4,5,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Carlson [4,5] has classified fiber types in the cat's lumbar back muscles using his tochemical methods in order to determine how the fiber composition of the various muscles relates to their con tracting properties. Ford et al [16,17] have compared paravertebral muscle fiber characteristics at different levels of the column in the Rhesus monkey in an effort to determine if this animal could be used as a model to study idiopathic scoliosis.…”
Section: Introductionmentioning
confidence: 99%
“…The highest mobility was also found in the presacral joint during manipulation of the anesthetized cat (Carlson, 1978) and the rock hyrax (Fischer, 1998). Despite the different directions of movements at symmetrical gaits in comparison to asymmetrical gaits (tilting and lateral bending versus sagittal bending), the largest motion was also measured at the lumbosacral junction in horses (Haussler et al, 2001).…”
Section: Sagittal Bending and Regionalization Of The Trunkmentioning
confidence: 99%
“…horses (Audigie et al, 1999;Faber et al, 2001;Haussler et al, 2001;Licka et al, 2001;Robert et al, 2001); dogs (Tokuriki, 1973a;Tokuriki, 1973b;Tokuriki, 1974;Jenkins, Jr and Camazine, 1977;Ritter et al, 2001); foxes (Jenkins, Jr and Camazine, 1977); cats (Jenkins and Camazine, 1977;Carlson et al, 1979;English, 1980); raccoons (Jenkins, Jr and Camazine, 1977); skunks (van der Graaff et al, 1982); ferrets (Kafkafi and Golani, 1998); tree shrews (Jenkins, Jr, 1974;Schilling and Fischer, 1999); primates (Shapiro et al, 2001); and grey short-tailed opossums (Pridmore, 1992)]; however, little information is available for asymmetrical gaits. Most studies investigated either 'pelvic motion' (Hildebrand, 1959;Jenkins, Jr and Camazine, 1977;Fischer et al, 2002) or X-rays of manipulated cadavers to comprehend the observed 'pelvic movement' (Alexander et al, 1985;Fischer, 1994;Carlson, 1978). Some more detailed data were published only for the pika (Fischer and Lehmann, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The different hindlimb and neck muscles contain different types of muscle fibers, and the sizes of hindlimbs and neck muscle motoneurons vary [1, 3-5, 13, 17]. Carlson [6,7] noted that Long Motoneurons include different types of motor units but mainly consist of fast units (Group 2 muscle fibers; more than 90%). The innervation ratio of each type of Long motoneuron has not been reported, though Carlson [6] seems to indicate that the Long motoneuron pool predominantly consists of larger motoneurons.…”
mentioning
confidence: 99%